Effects of Cyclosporine on Palmoplantar Pustulosis and Serum Expression of IL-17, IL-23, and TNF-α - Xian-Hua Jin; Xi Chen; Yan Mou; Jian-Xin Xia (Adis, Springer Healthcare, 2019)
Abstract Introduction This study aimed to investigate the effects of cyclosporine on palmoplantar pustulosis (PPP) and serum expression of IL-17, IL-23, and TNF-α. Methods Patients with PPP (n = 48) were recruited and treated with cyclosporine alone. The Palmoplantar Pustulosis Area and Severity Index score was obtained, and ELISA was employed to detect the serum IL-17, IL-23, and TNF-α expression before treatment and after 8 weeks of treatment. Results Complete remission was achieved in 16.7% of the patients, remission in 45.8%, an improvement in 31.3%, and the treatment was ineffective in 6.25%, yielding an overall effectiveness of 62.5%. Adverse effects included hypertension (n = 6), frequent urination and enuresis nocturna (n = 6), gastrointestinal discomfort (n = 6), hypertrichosis (n = 3), and increased creatinine (n = 1). While serum IL-17, IL-23, and TNF-α concentrations were reduced after 8 weeks of treatment, the reductions were greatest for IL-23 and TNF-α, whereas the reduction in IL-17 was not significant. Conclusion Cyclosporine is a safe and effective treatment for PPP with few adverse effects, which might be related to the regulation of IL-23 and TNF-α.